Swimming nanorobots for opening a cell membrane mechanically. Issue 3 (21st July 2020) - Wang, Wei; Wu, Zhiguang; He, Qiang
Abstract: Swimming nanorobots performing efficient self‐propulsion in various biofluids have drawn tremendous attention over 15 years due to their application including active drug delivery, precise cell manipulation, noninvasive surgery, rapid biosensor, and mobile in vivo imaging in the field of biomedicine. However, there are still many challenges in using swimming nanorobots in practice for active drug delivery and therapy, such as biocompatibility of chemical fuels or externally physical fields, biodegradation of synthetic materials, biofouling in bodily fluids, in vivo imaging of swimming nanorobots, and self‐navigation for active targeting. In this review, we highlight the mechanical drilling of cell membranes by swimming nanorobots and discuss the issues, because the cell membranes are one of the key barriers for intracellular drug delivery and drug delivery efficiency of swimming nanorobots. We will summarize the recent advances in swimming nanorobots with different propulsion mechanism and introduce the fundamental issues of interaction between swimming nanorobot and cell membrane. Then, the process, mechanism, and optimization of mechanically opening a cell membrane by swimming nanorobots are discussed and the perspective on the challenge and solution is also included. Such swimming nanorobots capable of mechanically opening a cell membrane could help to better understand the biophysical property of cells and pave the development of precision medicine. Abstract : Swimming nanorobot is a powerful technique to actively pass through various biological barriers. Swimming nanorobots capable of mechanically opening the cell membrane are reviewed, because the cell membrane is a key biological barrier for various biomedical applications ranging from drug delivery to artificial insemination.